PERANCANGAN KAWASAN TERMINAL ANGKUTAN SUNGAI YANG REKREATIF DI PURUK CAHU - Herda Marcellina; Ira Mentayani (JURNAL TUGAS AKHIR MAHASISWA LANTING, 2025)
Attention to the development of river transport terminals is very important because the river transport terminal facilities in Puruk Cahu City are not sufficient to accommodate the needs of community activities. As an area where many community activities are carried out on the banks of the Barito River, the existence of river transport terminal facilities is very crucial to support local transport connectivity. However, the development of river transportation infrastructure in this area is still limited and the need for adequate river transportation terminal facilities is very important. Apart from that, Dayak culture may face challenges in maintaining its authenticity. The aim of this design is to design a water transportation site that not only functions as a transit point, but also as an attractive and enjoyable tourist destination for visitors. Designing by considering cultural characteristics is also an effort to maintain and respect local cultural heritage. Based on this, the design of this river transport terminal area uses the Riverfront Architecture concept which uses two approaches, namely design based on local wisdom and sustainable design. The recreational river transport terminal area is the focal point in regional development river. It has the ability to improve the quality of life of local people, interesting tourists, and improve the tourist experience.